Evaluation of hydrocarbon flow standard facility equipped with double-wing diverter using four types of working liquids. (30th March 2017) - Doihara, R; Shimada, T; Cheong, K H; Terao, Y
Abstract: A flow calibration facility based on the gravimetric method using a double-wing diverter for hydrocarbon flows from 0.1 m 3 h −1 to 15 m 3 h −1 was constructed as a national measurement standard in Japan. The original working liquids were kerosene and light oil. The calibration facility was modified to calibrate flowmeters with two additional working liquids, industrial gasoline (flash point > 40 °C) and spindle oil, to achieve calibration over a wide viscosity range at the same calibration test rig. The kinematic viscosity range is 1.2 mm 2 s −1 to 24 mm 2 s −1 . The contributions to the measurement uncertainty due to different types of working liquids were evaluated experimentally in this study. The evaporation error was reduced by using a seal system at the weighing tank inlet. The uncertainty due to droplets from the diverter wings was reduced by a modified diverter operation. The diverter timing errors for all types of working liquids were estimated. The expanded uncertainties for the calibration facility were estimated to be 0.020% for mass flow and 0.030% for volumetric flow for all considered types of liquids. Internal comparisons with other calibration facilities were also conducted, and the agreement was confirmed to be within the claimed expanded uncertainties.